Spastic Paraparesis in Young Men With Spinal Meningioma and Spinal Arteriovenous Malformation: A Case Report - Leonard Christianto Singjie; Ivan Jeremia; Esdras Ardi Pramudita (Journal Orthopaedi and Traumatology Surabaya)
Background: Compared to trauma cases, the publication of non-traumatic events is much less, although the incidence is estimated to be as much as a traumatic event. This case report presents spinal cord tumors together with arteriovenous malformation (AVM) in young men, where there are no previous case reports that the authors can find.